2015
DOI: 10.1016/j.virol.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel arenavirus harbored by Rodents and Shrews in Zhejiang province, China

Abstract: To determine the biodiversity of arenaviruses in China, we captured and screened rodents and shrews in Wenzhou city, Zhejiang province, a locality where hemorrhagic fever diseases are endemic in humans. Accordingly, arenaviruses were detected in 42 of 351 rodents from eight species, and in 12 of 272 Asian house shrews (Suncus murinus), by RT-PCR targeting the L segment. From these, a single arenavirus was successfully isolated in cell culture. The virion particles exhibited a typical arenavirus morphology unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 21 publications
2
77
0
Order By: Relevance
“…Li et al . () identified a new arenavirus Wenzhou virus, in South China, with high prevalence in four rodent species, R. norvegicus, R. flavipectus, R. losea and R. rattus . Wenzhou virus was also detected in low prevalence in N. niviventer (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . () identified a new arenavirus Wenzhou virus, in South China, with high prevalence in four rodent species, R. norvegicus, R. flavipectus, R. losea and R. rattus . Wenzhou virus was also detected in low prevalence in N. niviventer (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we test our hypotheses using data from recent reports of newly emerging rodent‐borne arenaviruses in SEA (Li et al . ; Blasdell et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A pathogenic potential was suggested, but not confirmed initially. 12 It was then found that some patients in southeast Asian countries with respiratory symptoms tested positive for the Wenzhou virus. The virus was hypothesized to be spreading more widely among humans in Asia.…”
Section: Discovery Of New Potentially Pathogenic Microorganisms In Anmentioning
confidence: 99%
“…The recent discovery of erinaceus coronavirus (EriCoV) in West European hedgehogs (Erinaceus europaeus) indicates that insectivores are the natural reservoir of CoV (41). Over the past decade, additional novel viruses have been identified in shrews (29)(30)(31), indicating that these animals may play an important role in the evolution and transmission of viruses, including coronaviruses. WESV was identified in 24 of 266 shrews sampled from four counties of two provinces, with an overall detection rate of 9.02%, but not in rodents captured from the same areas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the discovery of distinct nidoviruses in insects suggests that coronaviruses may have an invertebrate origin (27,28). Importantly, multiple viruses (e.g., arenavirus, hantaviruses, and rotavirus) have also been identified in insect-eating shrews over the past decade (29)(30)(31). Hence, like bats, shrews may play an important role in the evolution and transmission of viruses, including coronaviruses, among animals, or from animals to humans.…”
mentioning
confidence: 99%